PERAN PEMERINTAH DAERAH DALAM MEMBERDAYAKAN UMKM DI KOTA SEMARANG (STUDI KASUS KAMPUNG BATIK KOTA SEMARANG) - Giovanni Malemta Purba; Purwoko . (Journal of Politic and Government Studies, 2018)
Micro, Small and Medium Enterprises (MSMEs) themselves are an important part of the economy of a country or region, not least in the city of Semarang itself. Semarang City is one of the big cities in Indonesia which is the capital city of the Central Java Province. Semarang itself is often known as an industrial city, trade and services. The city of Semarang itself is the capital of Central Java Province where this big city has a lot of potential based on its geographical and historical location. Semarang has a batik "Semarangan" which signifies the characteristics of the city of Semarang so that it can be said is one of the potential of the city of Semarang.Semarang city government itself has considered Semarang batik as a superior product of Semarang City because of its motifs and patterns that describe the city of Semarang itself, so that semarangan batik products are only found in the city of Semarang. This has also been included in the OVOP (One Village One Product) program in 2012 which means that Semarang batik has been considered and recognized by the Semarang City government as one of the superior products of Semarang City.In conducting research, researchers used descriptive qualitative research methods, this descriptive qualitative research aims to describe, record, analyze and interpret conditions that currently occur or exist. In other words, this qualitative descriptive study aims to obtain information about the existing conditions.The results of this study indicate that the role of government in empowering MSMEs in Semarang City's Bubakan Batik Village here, represented by the Semarang City Office of Cooperatives and MSMEs, has carried out the role of facilitator, regulator and catalyst, in its implementation according to the indicators. maybe and ready to facilitate, but there are still problems that occur because there is still no synergy between related agencies involved in empowering MSMEs and there is still no good communication between the agencies related to the UMKM actors themselves, plus the roles and responses of actors The UMKM itself is still not good at welcoming the efforts of the Semarang City Government.Keywords: MSMEs, role theory, empowerment indicators